Mechanisms and targeted prevention of hepatic osteodystrophy caused by a low concentration of di-(2-ethylhexyl)-phthalate - Hui, Qinming; Du, Xinru; Li, Maoxuan; Liu, Sha; Wang, Zhendong; Song, Sisi; Gao, Yancheng; Yang, Ye; Zhou, Chunxiao; Li, Yuan (Frontiers in Immunology, 2025)
ObjectivesHepatic osteodystrophy (HOD) is an important public health issue that severely affects human health. The pathogenesis of HOD is complex, and exposure to environmental pollutants plays an important role. Di-(2-ethylhexyl) phthalate (DEHP) is a persistent environmental endocrine toxicant that is present in many products, and the liver is an important target organ for its toxic effects. Our research aimed to investigate the effects of DEHP on HOD, and to reveal the underlying mechanisms and the potential key preventive approaches. MethodsThe daily intake EDI of DEHP and bone density indicators for men and women from 2009 to 2018 were screened and organized from the NHANES database to reveal the population correlation between EDI and BMD; C57BL/6 female and male mice were selected to construct an animal model of DEHP induced HOD, exploring the fuchtions and mechanisms of DEHP on osteoporosis; the novel small molecule inhibitor imICA was used to inhibit the process of DEHP induced osteoporosis, further exploring the targeted inhibition pathway of DEHP induced HOD.ResultsMale and female populations were exposed to a relatively lower concentration of DEHP, and that only the male population exhibited a negative correlation between DEHP exposure and bone mineral density. An in vivo study confirmed that a low dose of DEHP caused liver lesions, disrupted liver function, and induced osteoporosis in male but not female C57BL/6J mice. Regarding the molecular mechanisms, a low dose of DEHP activated the hepatic 14-3-3η/nuclear factor κB (NF-κB) positive feedback loop, which in turn modified the secretory proteome associated with bone differentiation, leading to HOD. Finally, we revealed that targeting the 14-3-3η/ NF-κB feedback loop using our novel 14-3-3η inhibitor (imICA) could prevent DEHP-induced HOD.ConclusionA low dose of DEHP activated the hepatic 14-3-3η/ NF-κB positive feedback loop, which in turn modified the secretory proteome associated with bone differentiation and elevated IL-6 and CXCL1 levels, leading to HOD. Targeted 14-3-3η/NF-κB feedback loop using our novel 14-3-3η inhibitor, imICA, prevented DEHP-induced HOD.